Measures to improve auditor efficiency in fraud detection. - Chan, Pearl Yan Yee. (2008)
This study focuses on the effects of the availability of the Beneish M-Score Model on the audit risk assessments and fraudulent earnings management detections by experienced and inexperienced auditors.